Once daily versus twice daily Linagliptin effect on glycemic levels in type 2 diabetes mellitus- an observational study - Mohammed, Riyaz; Ali, Mohammed Azfar (International Journal of Research in Medical Sciences, 2017)
Background: DPP-4 is widely distributed in endothelial cells, pancreas, uterus, liver, salivary glands, lymph node, spleen, and thymus. DPP-4 regulates glucagon-like peptide (GLP)-1, and glucose-dependent insulin tropic peptide (GIP) which leads to glucose homeostasis via enhancing insulin secretion and suppression of glucagon, which results in control of post-prandial and fasting hyperglycemia. Methods: These 40 patients who were enrolled as per the inclusion criteria of receiving metformin dosage of 2 gram per day in established type 2 diabetes mellitus patients with no comorbidities. these patients were divided randomly into two groups comprising of 20 patients each, group A received linagliptin 5 mg per day in addition to metformin 1gm twice daily whereas group B received linagliptin 5 mg per day in a fixed dose (Linagliptin + metformin) of 2.5/1000 twice daily. Results: In the present observational study, the mean age in group A was 46.7±9.4 compared to 51.65±9.9 in group B, p >0.05, mean BMI in group A was 27.8±1.1 compared to 27.28±0.93 in group B p >0.05, Mean FBS in group A was 157.9±24.1 compared to 146.2±21.8 in group B p >0.05, Mean PPBS in group A was 245.8±32.7 compared to 246.2±39.3 in group B p >0.05 and Mean HbA1c in group A was 7.67±0.58 compared to 7.6±0.5 in group B p >0.05. Group A patients were initiated on once daily linagliptin, there was a significant reduction in FBS, PPBS and HbA1c at the end of 6 months p <0.001. Similarly, Group B patients who were initiated on twice daily linagliptin also showed a significant reduction in FBS, PPBS and HbA1c at the end of 6 months p <0.001. Conclusions: The addition of linagliptin to metformin treatment was effective and well tolerated in patients with type 2 diabetes. Linagliptin add-on to metformin during the early course of treatment helps in delaying the exhaustion of pancreatic islet function. Plasma concentrations of linagliptin decline in at least a biphasic manner with a long terminal half-life (>100 hours), related to the saturable binding of linagliptin to DPP-4. The prolonged elimination phase does not contribute to the accumulation of the drug. Addition of linagliptin to metformin has shown a significant reduction in FBS, PPBS and HbA1c.